2019
DOI: 10.3389/fpsyg.2019.00420
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Against Burnout? An Individual’s Tendency to Engage in and Enjoy Thinking as a Potential Resilience Factor of Burnout Symptoms and Burnout-Related Impairment in Executive Functioning

Abstract: The personality trait need for cognition (NFC) refers to individual differences in the tendency to engage in and enjoy cognitive endeavors. In today’s working world, which is characterized by increasing cognitive demands, NFC may contribute to resilience against work-related stress and burnout symptoms. We investigated this question in a large population-wide sample of 4,134 individuals (Study 1) and in a sample of 125 students (Study 2). NFC was consistently negatively related to the burnout facets emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
(109 reference statements)
1
11
0
2
Order By: Relevance
“…However, in line with previous research (Bertrams & Dickhäuser, 2012a), the results indicate that NFC is at best weakly related to basic EF. They further confirm results of a recent study reporting no significant association of NFC to EF tasks for working memory updating (two-back), shifting (number-letter), and inhibitory control (Go-nogo;Fleischhauer et al, 2019). Complementary to the results reported here, mainly mental speed (and not basic EF) could be associated with NFC so that difference measures (i.e., IES) would disguise such effects.…”
Section: Discussionsupporting
confidence: 91%
“…However, in line with previous research (Bertrams & Dickhäuser, 2012a), the results indicate that NFC is at best weakly related to basic EF. They further confirm results of a recent study reporting no significant association of NFC to EF tasks for working memory updating (two-back), shifting (number-letter), and inhibitory control (Go-nogo;Fleischhauer et al, 2019). Complementary to the results reported here, mainly mental speed (and not basic EF) could be associated with NFC so that difference measures (i.e., IES) would disguise such effects.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that type 2 diabetics with higher NFC were more likely to remember relevant written diabetes information than patients low in NFC [44]. Of note, NFC has been already identified as a protective health factor such as in terms of burnout [45].…”
Section: Diabetes Self-management and Related Personality Factorsmentioning
confidence: 99%
“…Since recent effects regarding Need for Cognition (NFC) and burnout (e.g., Fleischhauer et al, 2019;Schmidt et al, 2012) are considerably smaller, the discovered effects of COM, SR and health-promoting/endangering behavior are quite astonishing and can be seen as a first confirmation for the notion of these traits being an important personal resource in work contexts.…”
Section: Discussionmentioning
confidence: 99%
“…High-NFC individuals tend to deal with these challenges by active (Grass et al, 2018) and problem-focused coping, resulting in more positive affect (Bye & Pushkar, 2009). Individuals with higher NFC feel better (Bertrams & Dickhäuser, 2012;Fleischhauer et al, 2010;Osberg, 1987) and show lower levels of neuroticism and symptoms of depression and anxiety (Bertrams & Dickhäuser, 2012;Epstein et al, 1996;Fleischhauer et al, 2019;Nishiguchi et al, 2016;Reeves et al, 1995;Sevincer et al, 2017). Additionally, Strobel et al (2021) assessed COM before in-patient's treatment in psychosomatic rehabilitation and reported a negative association with depressive symptoms after treatment.…”
Section: Self-regulative Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation